2017
DOI: 10.1111/ajt.14290
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Cold Ischemia Time Results in Local and Remote Organ Dysfunction in a Murine Model of Vascularized Composite Transplantation

Abstract: Vascularized composite allotransplantation (VCA) is a viable reconstructive option for complex tissue defects. Although grafts with a large muscular component may be uniquely susceptible to ischemia-reperfusion (I/R) syndrome, the safe cold ischemia time in VCA has not been established. We investigated the effects of cold ischemia on innate immune response and recipient survival in a murine orthotopic hindlimb transplantation model. Surprisingly, mice receiving grafts exposed to 6 h or longer of cold storage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Additionally, it is known that ROS production induced by mitochondrial dysfunction leads to structural and functional cell damages . Two distinct phases of cold ischaemia were observed up until 6 hours in this study, and our results confirm observations in several other organs, such as the liver and kidney . We confirmed that beyond 6 hours, islets started to lose function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, it is known that ROS production induced by mitochondrial dysfunction leads to structural and functional cell damages . Two distinct phases of cold ischaemia were observed up until 6 hours in this study, and our results confirm observations in several other organs, such as the liver and kidney . We confirmed that beyond 6 hours, islets started to lose function.…”
Section: Discussionsupporting
confidence: 91%
“…38 Two distinct phases of cold ischaemia were observed up until 6 hours in this study, and our results confirm observations in several other organs, such as the liver and kidney. [39][40][41] We confirmed that beyond 6 hours, islets started to lose function. However, we cannot exclude that this effect might be due to the use of HBSS and further studies using preservation solution would strengthen the study.…”
Section: Discussionsupporting
confidence: 70%
“…reperfusion phase, resulting in an increased incidence of acute and chronic rejection episodes, and organ failures. 3,4 In hand allografts, the critical time of cold ischemia resulting in permanent damage is currently unknown. According to the international hand transplantation registry, cold ischemia times ranged from 30 minutes to 13.5 hours (average 5.5 hours) in hand allografts.…”
mentioning
confidence: 99%
“…This wide variation may be one of the factors explaining the difference in function and long-term survival of hand allografts. 3,5,6 In this study, we aimed to investigate the long-term metabolic and structural effects of SCS on limb allografts using a syngeneic rat hindlimb allograft model. A syngeneic model represents all characteristics of VCAs without the need for immunosuppression.…”
mentioning
confidence: 99%
“…In a mouse orthotopic hindlimb transplant model, for example, prolonged ischemic times have been associated with diminished graft survival. 64 Notably, tolerable ischemic times have not been established for VCA grafts. Utilizing standard preservation methods, cold ischemic times up to 6 h have been cited as an upper threshold in VCAs.…”
Section: Vcas: a Complex Interplay Between Innate And Adaptive Immunitymentioning
confidence: 99%